Desempenho motor em crianças pré-termo e a termo aos quatro, seis e oito meses de idade: estudo comparativo - Patricia de Faria Megale Lino (2008)
Objective: To compare the motor performance of preterm and full term infants aged four, sis and eight months.Method: observational, longitudinal and prospective study. The Alberta Infant Motor Scale- AIMS- was used to evaluate 44 infants (22 preterm and 22 full term) The full term group included 12 female and 10 male infants, and the preterm group included 11 female and 11 male infants. Gestational age was corrected for the preterm group. The examiner was blinded to group membership. Data analysis included intraclass correlation to verify inter-rater reliability and, since the Shapiro- Wilk test did not confirm that the data was normally distributed, the Mann-Whitney test was used to compare the two groups and the Wilcoxon s test to compare the AIMSs percentiles in the same group, at different ages (p< 0,05). The correlation between variables (Spearman) was examined as well as the differences in item performance (Chi- squared).Results: Mann-Whitneys test did not identify significant difference between groups on motor performance in any of the ages, either for total and area scores or percentiles. But there were signs of variation in rhythm and instability of the percentiles.Concluson: The results support the idea of possible variations in individual evaluations of motor development, and aspect that is relevant for professionals who work in the infant development area.